Pola Pertumbuhan Dan Faktor Kondisi Ikan Brek (Barbonymus balleroides val. 1842) Di Perairan Pulau Jawa Koleksi Museum Zoologi Bogoriense (MZB) - Maizul, Riza; Setyawati, Siti Mukhlishoh; Wahyudewantoro, Gema (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Brek fish (Barbonymus balleroides) is a consumption, fish that is widely used by people around the River. The population has started to decline, but not yet cultivated. Therefore, research has been conducted as a basis for its domestication, including growth patterns and condition factor of Brek Fish. The total length (TL) of each individual was measured using a digital caliper with an accuracy of 0.05 mm, while the body weight was weighed using an analytical scale with an accuracy of 0.0001 g. the data obtained were analyzed by linear regression found in the microsoft excel program. The results showed that the growth pattern of brek fish was allometric negative, the average condition factor value of brek fish (B. balleroides) was 1.026. The author hopes this research can be used as basic biological information to support the conservation of Brek Fish (B. ballerodes).